2012
DOI: 10.1007/s10120-011-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the utility of EUS for preoperative staging for gastric cancer

Abstract: Background Accurate preoperative staging is important in determining the appropriate treatment of gastric cancer. Recently, endoscopic ultrasound (EUS) has been introduced as a staging modality. However, reported test characteristics for EUS in gastric cancer vary. Our purpose in this study was to identify, synthesize, and evaluate findings from all articles on the performance of EUS in the preoperative staging of gastric cancer. Methods Electronic literature searches were conducted using Medline, Embase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 40 publications
2
106
0
2
Order By: Relevance
“…If determination of organ invasion is necessary, a highercapacity scanner may give more accurate results (T1: 75.2 vs. 47.5% and T3: 84.5 vs. 69.3% for C4 detector and \4 detector scans, respectively, Table 6). Accurate staging of T1 versus T2 is important for endoscopists considering endoscopic mucosal resection (EMR) and may be aided by using EUS [64,65], whereas accurate staging of T3 versus T4 is important as the surgeon would need to plan a multivisceral resection. The use of MPR images significantly improved T staging performance compared to axial images alone, resulting in a substantial agreement with pathology (j = 0.67), an overall accuracy of 82%, and stage-specific accuracies ranging from 76 to 85% (Table 6).…”
Section: Evaluation Of T Stagingmentioning
confidence: 99%
“…If determination of organ invasion is necessary, a highercapacity scanner may give more accurate results (T1: 75.2 vs. 47.5% and T3: 84.5 vs. 69.3% for C4 detector and \4 detector scans, respectively, Table 6). Accurate staging of T1 versus T2 is important for endoscopists considering endoscopic mucosal resection (EMR) and may be aided by using EUS [64,65], whereas accurate staging of T3 versus T4 is important as the surgeon would need to plan a multivisceral resection. The use of MPR images significantly improved T staging performance compared to axial images alone, resulting in a substantial agreement with pathology (j = 0.67), an overall accuracy of 82%, and stage-specific accuracies ranging from 76 to 85% (Table 6).…”
Section: Evaluation Of T Stagingmentioning
confidence: 99%
“…Conversely, patients with advanced gastric cancer may miss out on beneficial preoperative treatment if their disease is understaged. Several reports and meta-analyses regarding the accuracy of preoperative EUS T staging have been published (7)(8)(9)(10), but the reported accuracies differed substantially (8). Furthermore, studies of preoperative staging accuracy that focus on patient selection for preoperative therapy are rare; therefore, whether EUS can reliably identify patients eligible for preoperative therapy (i.e., those with stage T2 or higher lesions) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There were two systematic reviews assessing diagnostic accuracy of EUS for the staging of GC in previous years. Cardoso et al 35 found that EUS was a moderately accurate technique for both T and N staging. Mocellin et al 36 found that the sensitivity of the single T categories (T1, T2, T3 and T4) for EUS were 83%, 65%, 86% and 66%, respectively, and the specificity were 96%, 91%, 85% and 98%, respectively.…”
Section: Discussionmentioning
confidence: 99%